Penguatan Citra, Tata Ruang, Produk, dan Pelayanan Arda Koffie Dalam Upaya Peningkatan Jumlah Pelanggan - Rahayu, Ana Duwi; Maulana, Eno; Hidayana, Nefi; Azizah, Siti Mufidatul; Rahmawati, Linda; Rahmawati, Dyan; Afifah, Charista Tanta Putri lis; Avifah, Nur (Welfare : Jurnal Pengabdian Masyarakat, 2024)
This article discusses community service through internship programs. This article applies a strategy that focuses on strengthening image, layout, products and services. Facing increasingly tight competition in the cafe industry, Arda Koffie is increasing the number of customers by strengthening its position by building a strong brand image, creating a more attractive and comfortable layout, and improving the quality of products and services. The approach implemented involves in-depth analysis of the brand image to understand customer perceptions and expectations, as well as identify aspects that need improvement. The spatial redesign was carried out to create a more aesthetic and functional atmosphere, thereby improving customer comfort and experience. Improving product quality is carried out optimizing service is focused on increasing customer interaction and satisfaction. By implementing this strategy, Arda Koffie is expected to be able to attract more customers, increase satisfaction and strengthen customer loyalty. It is hoped that the success of this program will support the sustainability and growth of Arda Koffie's business in the future.